2019
DOI: 10.31219/osf.io/u9pbm
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The Environmental Context of the Earliest Acheulean at Olduvai Gorge, Tanzania

Abstract: Water, vegetation, and human habitats are tightly coupled, and Olduvai Gorge, Tanzania is an exceptional locality for examining evolutionary events that associate with water availability and environmental stability or change. This project investigates interactions between and among paleo-hydrology, habitat type, and the human response to changing environmental settings. The objective is to interpret the climate and environmental context of the oldest Acheulean stone tool industry at Olduvai Gorge using plant l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
21
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

4
1

Authors

Journals

citations
Cited by 6 publications
(21 citation statements)
references
References 0 publications
0
21
0
Order By: Relevance
“…Plant wax lipid extraction and analysis is now being applied in archaeology contexts to investigate human‐environment interactions (Brittingham et al., 2019; Colcord et al., 2018; Collins et al, 2017; Connolly et al., 2019; Lupien et al., 2018; Magill, Ashley, & Freeman, 2013a, 2013b; Magill, Ashley, Domínguez‐Rodrigo, & Freeman, 2015; Patalano, 2019; Uno et al., 2016). Because n ‐alkanes and n ‐alkanoic acids record ancient environmental conditions through δ 13 C and δD ratios, they can track variations in hydroclimate, vegetation community and structure, and habitat type and be used to investigate human biological and cultural adaptive responses to ecological changes.…”
Section: Commentarymentioning
confidence: 99%
See 1 more Smart Citation
“…Plant wax lipid extraction and analysis is now being applied in archaeology contexts to investigate human‐environment interactions (Brittingham et al., 2019; Colcord et al., 2018; Collins et al, 2017; Connolly et al., 2019; Lupien et al., 2018; Magill, Ashley, & Freeman, 2013a, 2013b; Magill, Ashley, Domínguez‐Rodrigo, & Freeman, 2015; Patalano, 2019; Uno et al., 2016). Because n ‐alkanes and n ‐alkanoic acids record ancient environmental conditions through δ 13 C and δD ratios, they can track variations in hydroclimate, vegetation community and structure, and habitat type and be used to investigate human biological and cultural adaptive responses to ecological changes.…”
Section: Commentarymentioning
confidence: 99%
“…Typically, microbial reworking of leaf waxes results in UCM distributions with chromatographic outputs between C 16 and C 22 (Grimalt et al., 1988). Fortunately, this does not overlap with the retention window for higher‐chain n ‐alkanes, and many samples will have slight evidence for microbial activity that does not interfere with GC‐MS/IRMS analyses; in fact, even relatively modern topsoils can exhibit UCMs (Patalano, 2019). In extensively reworked samples, on the other hand, the severity of the UCM may completely obscure the n ‐alkanes, making it impossible to obtain any reliable data.…”
Section: Commentarymentioning
confidence: 99%
“…Engaging in what palaeoanthropologists called a 'multi-proxy approach' , researchers examined an amalgamation of various traces of past environments that they had excavated -such as biomarkers and phytoliths -in order to clarify the environmental conditions that may have influenced hominins to change their patterns of behaviour and to develop the Acheulean stone tool industry roughly a million and a half years ago. Lipid 'biomarkers' , such as normal (n-) alkanes, are chemically inert organic compounds that resist biodegradation throughout extremely large stretches of time, and analysing the isotopic values of biomarkers that are found in the sediments that surround buried stone tools can reveal changes in past plant composition and availability of water (Eglinton and Eglinton, 2008;Patalano, 2019). Biomarker research that SDS scientists conducted confirmed a drying and warming trend at an Oldupai Gorge site in the deep past, and demonstrated that the site was likely a riverine forest surrounded by a mosaic-like landscape that featured both heavily treed areas and more open environments (Patalano et al, 2017).…”
Section: Palaeoanthropological Droughtmentioning
confidence: 99%
“…Lipid 'biomarkers' , such as normal (n-) alkanes, are chemically inert organic compounds that resist biodegradation throughout extremely large stretches of time, and analysing the isotopic values of biomarkers that are found in the sediments that surround buried stone tools can reveal changes in past plant composition and availability of water (Eglinton and Eglinton, 2008;Patalano, 2019). Biomarker research that SDS scientists conducted confirmed a drying and warming trend at an Oldupai Gorge site in the deep past, and demonstrated that the site was likely a riverine forest surrounded by a mosaic-like landscape that featured both heavily treed areas and more open environments (Patalano et al, 2017). Another trace of the past are 'phytoliths' , which begin to form when live plants absorb silica and the silica subsequently fills cell spaces.…”
Section: Palaeoanthropological Droughtmentioning
confidence: 99%
“…While climatic and environmental variability have been prominently discussed in influencing the broad patterns of human evolution, 1–5 linking ecosystem changes to technological and behavioral responses remains challenging. To address such research challenges, the analysis of plant wax lipids from ocean and lake cores, 6–8 paleo‐lake drilling projects, 9–13 archeological and geological outcrops, 14–18 cave deposits, 19–21 and hominin‐bearing sediments 22 have the potential to provide well‐integrated, high‐resolution data on past plant ecology and environmental stresses in regions where hominins evolved.…”
Section: Introductionmentioning
confidence: 99%